YR Moonwalking Experience - Rosa Burgess, Robin Charles (2017)
Ilinx, or vertigo play, is one of the four types of play identified by Roger Caillois[1]. While the application of this aspect of play to digital environments has been limited, attempts have been made to explore its potentials, with the use of virtual reality technology being a large part of it. In this context, Visual-Kinaesthetic Experiences have been defined as experiences where a virtual environment is visually overlaid over an existing kinaesthetic experience to create a new thrilling experience. The VR Moonwalking Experience explores the potential for using partial submersion in water to both simulate a virtual low gravity environment and to open up new pos¬sibilities in the design of new Visual-Kinaesthetic Experiences. The system places users in a virtual environment featuring a crater-filled lunar surface, with a star-filled sky, the distant earth, and a lunar module. At the same time, players stand in a swimming pool, the water level somewhere between their waist and chest, and jump in a motion imitating moonwalking. The system detects the player’s jumping and mirrors it synchronously in the virtual world, but exag¬gerates the height of the jump arc. To protect the equipment from splashing water